Quercetin Attenuates High-Fat Diet-Induced Excessive Fat Deposition of Spotted Seabass (Lateolabrax maculatus) Through the Regulatory for Mitochondria and Endoplasmic Reticulum - Dong, Yan-Zou; Xia, Tian; Lin, Ji-Bin; Wang, Ling; Song, Kai; Zhang, Chun-Xiao (Frontiers in Marine Science, 2021)
This study was conducted to investigate the effect of dietary quercetin on hepatic fat deposition and reveal its underlying mechanism. The fish were fed normal fat diet (NFD), high fat diet (HFD) and HFD supplemented with 0.05% or 0.1% quercetin (HFD+0.05%Q or HFD+0.1%Q) for 8 weeks. The results showed that HFD fed resulted in poor growth performance and feed utilization, while quercetin administration reversed this state. The serum and liver lipid contents were obviously increased by HFD fed, while quercetin supplementation significantly decreased lipid content. Furthermore, it was evidenced by the related gene expression and ultrastructural observation that mitochondrial biogenesis and mitophagy were inhibited by HFD, accompanied by endoplasmic reticulum stress (ERS) activation. Quercetin exhibited the activation effects of mitochondrial biogenesis and mitophagy and the suppression effect of ERS. In general, the present study demonstrated that quercetin attenuated excessive fat deposition via mitochondria and endoplasmic reticulum protection.